Safety, efficacy and repeatability of a novel house dust mite allergen challenge technique in the Fraunhofer allergen challenge chamber - Lueer, K.; Biller, H.; Casper, A.; Windt, H.; Mueller, M.; Badorrek, P.; Haefner, D.; Framke, T.; Koch, A.; Ziehr, H.; Krug, N.; Koch, W.; et al. (Allergy (Copenhagen), 2016)
Background Efficacy testing of immunotherapy in field studies is often hampered by variation of airborne allergens. Standardized allergen exposure in challenge chamber settings might be an alternative. Therefore, we developed a universal technique to create an atmosphere loaded with allergen particles of adjustable size from aqueous solutions of licensed allergen extracts. Objective The aim of this study was to apply this technique and test the safety and efficacy of challenges with house dust mite (HDM) allergen in the Fraunhofer allergen challenge chamber. Methods Aerosol particles carrying HDM allergen were produced by spray‐drying of an aqueous solution containing HDM allergen and lactose. In a monocenter, placebo‐controlled, single‐blind, dose‐escalation pilot study, 18 subjects with perennial allergic rhinitis and sensitization to HDM were exposed to HDM allergen for 4 h at either 250, 500, 1000 SQE/m3 or lactose alone (0 SQE/m3) 7 days apart. The dose of 500 SQE/m³ was repeated to investigate reproducibility. Total nasal symptom score (TNSS) was the primary endpoint. Results Exposure to HDM increased TNSS (mean ± SD) to 3.4 ± 1.8, 3.3 ± 2.1, and 3.6 ± 2.0 at 250, 500 and 1000 SQE/m3, respectively, while lactose alone did not change TNSS (0.7 ± 0.6). The results were reproducible at 500 SQE/m3. Pulmonary function and adverse event frequency did not change with escalation of allergen dose. Conclusion This HDM allergen particle generation is safe, specific and reproducible and can therefore be used for efficacy testing of immunotherapy and for basic clinical research.